THE DEVELOPMENT OF HACKING BASKET TORENIA BY USED INTERSPECIFIC CROSSES BETWEEN COMMERCIAL TORENIA AND TORENIA HIRSUTISSIMA, A WILD SPECIES OF THAILAND - Laojunta, Tanapoom; Boonmee, Sutjaritpan (Life Sciences and Environment Journal, 2025)
Pollen viability was found only in Mon Thian Thong (T. hirsutissima) and Summer Wave Large Amethyst with 33.25 % and 18.75 % pollen viability, respectively. Whereas non-viable pollen was found in Yellow Moon, Summer Wave Blue, and Summer Wave Amethyst cultivars. The study of pollen germination on synthetic media with 10% sucrose found that only Mon Thian Thong and Summer Wave Large Amethyst cultivars showed 25.25% and 5.75% pollen germination, respectively. The interspecific hybridization, T. ‘Summer Wave Large Amethyst’ × T. hirsutissima, found 6.66% pod setting and only 8.5 ovules per pod, where only 12% were developed in the plantlets. In other hybrids, meanwhile, could not produce pods from hybridization. Comparison of flower morphology revealed that the hybrids exhibited flower color characteristics of both parents. The disorganized arrangement of epidermal cells could be inherited from the parent to the hybrids. Additionally, the Mon Thian Thong cultivar exhibited the highest number of stomata per area, at 5.62 stomata per 10,000 square micrometers, followed by hybrid no.1 and hybrid no. 2. Whereas the Summer Wave Large Amethyst cultivar exhibited the least number of stomata per area, at 2.87 stomata per 10,000 square micrometers. All hybrids are true triploid hybrids, which are from a tetraploid (Summer Wave Large Amethyst) and a diploid (Mon Thian Thong).